COBIT as a Framework for Evaluating Strategic Business IT Alignment:Systematic Literature Review - Abdul Muis; Mukhammad Andri Setiawan (STMIK Widya Cipta Dharma, 2026)
Strategic business IT alignment is a critical factor in the success of organizational IT governance. Numerous studies have examined the use of COBIT in the context of IT governance and business IT alignment across various sectors. These studies are generally partial and limited to specific contexts or COBIT domains, resulting in a lack of a comprehensive understanding of cross sectoral patterns in the use of COBIT and the evaluation approaches applied. This literature review aims to map the use of COBIT as a framework for evaluating IT business alignment across different sectors, including the COBIT domains and evaluation approaches employed. This study adopts a Systematic Literature Review (SLR) approach following the PRISMA guidelines, which consist of identification, screening, and final selection stages. The review results indicate that COBIT implementation is distributed across four sectors, namely education (35,29%), industry (29,41%), government and healthcare (each 17,65%), with the education sector being dominant context. The APO domain is the frequently used domain, followed by EDM, DSS, BAI, and MEA. Collectively, these domains reflect an evaluation focus on strategic planning, resource management, risk management, IT service delivery, and monitoring and evaluation mechanisms. The evaluation approaches identified in the reviewed literature are predominantly assessment-based, followed by IT governance design approaches, while comparative and exploratory approaches are used in a limited number of studies. The results of this review contribute by providing a structured overview of the patterns of COBIT domain usage and evaluative approaches across sectors. These findings may serve as a reference for future research as well as for practical evaluations of business and IT strategic alignment.